Intensitas Tekanan dan Kinerja Tim di Liga 1 Indonesia 2024/25: Bukti dari OHDA dan DLH - Asep Sumpena; Reshandi Nugraha; Dikdik Zafar Sidik; Hendri Munar (Faculty of Sport and Health Sciences, 2025)
This study examined pressing intensity in the 2024/25 Indonesia Liga 1 season by analysing defensive line height, defensive actions in the opponent’s half, and their relationship with team performance. Using a cross-sectional design, secondary aggregate data from all 18 clubs were analysed through descriptive statistics, Spearman correlation, and regression analysis. Defensive line height reflected the average positioning of a team’s defensive unit, while opponent-half defensive actions represented the frequency of pressing in advanced areas. The results showed a negative correlation between defensive line height and final league ranking, indicating that teams with higher defensive positioning tended to achieve better standings. Defensive actions in the opponent’s half were positively associated with total points, suggesting that more aggressive pressing may contribute to improved performance. Regression analysis revealed that defensive line height explained 32% of the variance in points obtained. Sensitivity analysis further suggested that lower defensive line height may support counterattacking effectiveness, whereas higher opponent-half defensive actions were linked to goals from open play. Overall, pressing-related indicators provide valuable insights into team performance and may help coaches design tactical periodization and position-specific conditioning programs.